Phenotype and function of MAIT cells in patients with alveolar echinococcosis - Li, Jintian; Zhao, Hanyue; Lv, Guodong; Aimulajiang, Kalibixiati; Li, Liang; Lin, Renyong; Aji, Tuerganaili (Frontiers in Immunology, 2024)
Mucosal-associated invariant T (MAIT) cells are a subpopulation of unconventional T cells widely involved in chronic liver diseases. However, the potential role and regulating factors of MAIT cells in alveolar echinococcosis (AE), a zoonotic parasitic disease by Echinococcus multilocularis (E. multilocularis) larvae chronically parasitizing liver organs, has not yet been studied. Blood samples (n=29) and liver specimens (n=10) from AE patients were enrolled. The frequency, phenotype, and function of MAIT cells in peripheral blood and liver tissues of AE patients were detected by flow cytometry. The morphology and fibrosis of liver tissue were examined by histopathology and immunohistochemistry. The correlation between peripheral MAIT cell frequency and serologic markers was assessed by collecting clinicopathologic characteristics of AE patients. And the effect of in vitro stimulation with E. multilocularis antigen (Emp) on MAIT cells. In this study, MAIT cells are decreased in peripheral blood and increased in the close-to-lesion liver tissues, especially in areas of fibrosis. Circulating MAIT exhibited activation and exhaustion phenotypes, and intrahepatic MAIT cells showed increased activation phenotypes with increased IFN-γ and IL-17A, and high expression of CXCR5 chemokine receptor. Furthermore, the frequency of circulating MAIT cells was correlated with the size of the lesions and liver function in patients with AE. After excision of the lesion site, circulating MAIT cells returned to normal levels, and the serum cytokines IL-8, IL-12, and IL-18, associated with MAIT cell activation and apoptosis, were altered. Our results demonstrate the status of MAIT cell distribution, functional phenotype, and migration in peripheral blood and tissues of AE patients, highlighting their potential as biomarkers and therapeutic targets.